1998
DOI: 10.1039/a708427g
|View full text |Cite
|
Sign up to set email alerts
|

Determination of copper and arsenic in refined beet sugar by stripping voltammetry without sample pretreatment

Abstract: Copper and arsenic have been analysed in refined beet sugar at the microgram kg-1 level by anodic stripping voltammetry (copper) and cathodic stripping voltammetry (arsenic) in the differential-pulse mode (DPASV and DPCSV) at a hanging mercury drop electrode (HMDE). DPCSV measurements of arsenic are based on its accumulation onto the HMDE as an intermetallic Cu-As compound followed by the reduction of As0 to arsine in hydrochloric acid medium. Measurements were directly carried out on untreated sugar solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The highest amount was found in cocoa based candy sample and the lowest in fruit based one (Table 4). In the literature copper levels in selected sweets of different shops of Karachi city have been reported in the range of 0.07-4.0 ppm (Naqvi et al 2004), in sugar samples produced by Spanish sugar beet refineries have been reported in the range of 16-47 μg/kg (Sancho et al 1998), in chewing gum samples have been reported in the range of 1.60-5.38 μg/g (Kilic et al 2002).…”
Section: Resultsmentioning
confidence: 95%
“…The highest amount was found in cocoa based candy sample and the lowest in fruit based one (Table 4). In the literature copper levels in selected sweets of different shops of Karachi city have been reported in the range of 0.07-4.0 ppm (Naqvi et al 2004), in sugar samples produced by Spanish sugar beet refineries have been reported in the range of 16-47 μg/kg (Sancho et al 1998), in chewing gum samples have been reported in the range of 1.60-5.38 μg/g (Kilic et al 2002).…”
Section: Resultsmentioning
confidence: 95%
“…The digestion of organic material is not always a must: for example, the same results were obtained for the determination of total arsenic and copper (detection limit of 2 ppb) in refined beet sugar with or without pretreatment [98].…”
Section: Natural Watersmentioning
confidence: 60%
“…MDEs are much less common (e.g., in [98]) because of the already mentioned low solubility of arsenic in this metal. Probably for the same reason, there is only one example of Hg-modified graphite electrodes and another of graphite electrodes with adsorbed HgI 2À 4 [99,100].…”
Section: Voltammetric Determination Of Arsenic At Trace Levelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, because of the compactness, simplicity, and low price of its equipment, stripping voltammetry is promising for field analysis and analysis in mobile laboratories and can become widespread in food laboratories, especially in underdeveloped countries. Stripping voltammetry is used to analyze wine and drinks [3]; milk and dairy produce [4]; standard reference samples of meat, liver, and fish [4,5]; seafood [6,7]; vegetables and spinach [7,8]; beet sugar [9]; etc. [10].…”
mentioning
confidence: 99%